Gridded GDP Projections Compatible With the Five SSPs (Shared Socioeconomic Pathways) - Murakami, Daisuke; Yoshida, Takahiro; Yamagata, Yoshiki (Frontiers in Built Environment, 2021)
Historical and future spatially explicit population and gross domestic product (GDP) data are essential for the analysis of future climate risks. Unlike population projections that are generally available, GDP projections—particularly for scenarios compatible with shared socioeconomic pathways (SSPs)—are limited. Therefore, we estimated the GDP in a 1/12-degree grid scale for the period of 1850–2100 in 10-year intervals. The estimation is done through downscaling of historical GDP data for 1850–2010 and SSP future scenario data for 2010–2100. In the downscaling, we first modeled the spatial and economic interactions among cities and projected different future urban growth patterns according to the SSPs. Subsequently, the projected patterns and other auxiliary geographic data were used to estimate the gridded GDP distributions. Finally, the GDP projections were visualized via three-dimensional mapping to enhance the clarity for multiple stakeholders. Our results suggest that the spatial pattern of urban and peri-urban GDP depends considerably on the SSPs; e.g., the GDP of the existing major cities grew rapidly under SSP1, slowly grew under SSP3, and dispersed growth under SSP5.